Out Scaling of Community-Based Breeding Programmes: Attractive and Innovative Approach to Improving the Lives of Smallholder Producers in Low-Input Systems - Hyera, Emil (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Community-based breeding programmes (CBBPs) are currently suggested as justifiable options for genetic improvement and conservation of the local indigenous small ruminant populations in developing countries. The CBBPs are planned to improve the productivity and adaptability of indigenous sheep and goats by choosing outstanding animals for the breeding goal traits for propagation within breed kinds, continuously sustained husbandry practices, and leaving out the inferior animals. This package of knowledge involves broad cooperation with diverse actors; combines training of farmers on animal husbandry, breeding practices and selection methods to stimulate genetic improvement within the flocks; embraces pooling community flocks to generate a larger gene pool from which breeding animals can be selected and to prevent the threat of inbreeding; and ensures close technical follow-up and backstopping to provide farmers with information on diverse breeding decisions and capacities to estimate individual animal performance, and make them self-reliant. Also, this approach considers smallholder farmers' constraints, supports views and decision-making at the local level, and establishes authorized farmers' cooperatives in low inputs production systems to warranty functionality and sustainability of the genetic improvement intervention.